Adapting Ukrainian Medical Education to the Challenges of War: A Scoping Review - Chavarha, M.; Suprunenko, S.; Shpryakha, Ya.; Gai, L.; Glavatskyi, O. M.; Главацький, Олександр Миколайович (My University, 2025)
Introduction: the war in Ukraine, which began in 2014 and escalated into a full-scale invasion in 2022, significantly transformed teaching methods in higher education. The skills acquired during distance learning amid the COVID-19 pandemic in 2019 proved valuable, especially in medical education, where mastering practical skills typically requires in-person practice at the patient’s bedside, in operating rooms, and laboratories. Method: to address the challenge of acquiring practical skills remotely, simulation methods were introduced, applicable both in simulation centers and through virtual simulation technologies. A systematic review was conducted to generalize and analyze research publications on the integration of simulation teaching methods into the medical education system. A total of 32 publications were selected according to systematic review standards. The literature search was conducted from 2019 to 2024 using the keywords “simulation learning,” “virtual reality,” “mixed reality,” “medical education,” and “distance learning” on the Scopus and PubMed platforms. The systematization of the analyzed literature was performed using the PRISMA program. Results: the review identified the main areas of implementation of virtual simulation tools in the educational process. The analysis highlighted how these tools contribute to the development of practical skills and enhance the overall learning experience for medical students during distance learning. Conclusions: the use of simulation training in medical education represents significant progress, improving the quality of training for medical professionals and ensuring the effective development of practical skills, even in remote learning conditions.
Keywords: Simulation Technologies; Crisis Management of Education; Integration of Military Medicine; Modernization of Educational Programs